Kebersinggungan Tarekat Dengan Dunia Luar Dalam Pandangan Martin Van Bruinessen - Misbakhul Khaer (Prodi Tasawuf dan Psikoterapi Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2022)
Whether we realize it or not, pursuing and practicing Sufism until it reaches the point that there is nothing but lillah, is not easy and only certain people can get there. For ordinary people, maybe just crawling in the early stages is already heavy, because the initial step for practitioners of Sufism is to stay away from worldly luxuries which incidentally everyone cannot completely escape from worldly affairs, especially in the modern era like today. Sufism and tarekat discourses have attracted the attention of many Muslim and western scholars. One of them is a Dutch orientalist named Martin Van Bruinessen. Martin describes in great detail how the portraits of the tarekat from the initial source, which then proceeded and reproduced in Indonesia. He also explained how the tarekat's close relationship with the local ruling elite and what radical efforts were carried out by tarekat adherents in order to defend their homeland from Dutch colonialism. The motivation of the ruler to approach the tarekat is to legitimize his power in front of the people. They consider the tarekat as a spiritual force, so that it becomes a wasilah for the continuity of its power and prosperity for its people. The contact between the tarekat and the political world occurs not only at the lower level, but also at the elite level. As for the Dutch colonial era, some tarekat in the past still thought that the Dutch were a people to be hostile to, in addition to the many implementations of the policies of the Dutch East Indies government, especially in the economic field which were not in favor of the people. In fact, it often causes resistance, so that in history there have been various kinds of wars between the people, involving religious leaders and tarekat with the Dutch KNIL soldiers.